EXPLORING POLITENESS STRATEGIES IN ‘A WALK TO REMEMBER’ MOVIE: A SOCIOLINGUISTIC APPROACH - Kasim, Hardiansyah; Satria, Robby (Universitas Putera Batam, 2024)
The primary objective of this research is to determine the many types of politeness tactics and the prevalent ones in the film